(untitled) (The Batuk, 2023)
In today’s digitalized workplace, workplace incivility and cyberloafing have become major concerns for many corporate and government organizations all over the world. The objective of this study was to determine the effects of cyberloafing and workplace rudeness on workers. The study took a quantitative approach, administered a set of survey questionnaire, and collected response from 135 employees from three rural municipalities in Kaski district. Different descriptive and inferential statistical analysis tools were applied to draw the conclusion. Results showed that the cyber loafing and employee productivity had a weak significant positive relationship (0.320) whereas work incivility and employee productivity had a negative co-relationship (-0.304). Similarly, the regression result reveled a significant low magnitude of impact of cyberloafing and workplace incivility (0.443 and -0.445 coefficient respectively) on employee productivity. This research underlines the necessity for local governments to put policies in place that discourages uncivil behavior at workplace and prevent employees from the tendency of cyberloafing, as doing so can help to increase worker productivity.